Impact of predatory mites (Acari: Phytoseiidae) associated with the cassava crop on Mononychellus spp. in the Colombian Atlantic coast. - HERRERA-F., CARLOS JULIO; GUERRERO, JOSÉ MARÍA; BRAUN, ANN R. (Revista Colombiana de Entomología, 1994)
Tetranychid mites are important pests in cassava growing zones with prolonged dry seasons. We studied the phenology, population dynamics, and impact of phytophagous and predatory mites in three subhumid sites on the Colombian North Coast. A different phytophagous and predatory mite complex occurred in the eách site. Mononychellus caribbeanae (McGregor) was the predominant tetranychid in the driest site (Fonseca). On the other sites, M. tanajoa was the most important species. In the driest site, the phytoseiid Amblyseius idaeus (Denmark & Muma) occurred throughout the sampling period surviving a rainless period of 3 months. A. limunicus s.l. (Garman & McGregor) was the predominant phytoseiid in the other zones. In Ciénaga de Oro, A. limonicus s.l. first appeared after a dry period of three months and persisted through two further dry months and the subsequent wet season. A. limonicus s.l. numbers increased in response to population growth of M. tanajoa, however high densities of this predator were observed when prey density was low. In Pivijay, the appearance of A. limonicus s.l. coincided with the population peak ofM. tanajoa. Subsequently, M. tanajoa decline., howeverA. limonicus s.l. persisted through the wet season in the virtual absence of tetranychid prey. In Fonseca, the intensity of Mononychellus attack was approximately 5 times greater than in Ciénaga de Oro. A. idaeus numbers responded to changes in M. caribbeanae andM. tanajoa density. In plots where natural enemies were present, fresh root yield was double that of plots where predators were eliminated. In both sites predators reduced the mite population by more than 50% compared to plots where predators were eliminated.